#BlueGirl: A study of collective trauma on Twitter. Issue 6 (2nd August 2022) - Abtahi, Zahra; Zahedi, Leila; Eizadyar, Zarrin; Fava, Nicole M.
Abstract: Collective trauma is the outcome of traumatic incidents that necessitate collective self‐reflection and create a need for public discourse. Access to social media allows individuals to shape event coverage beyond what is put forth by mainstream media through hashtag‐based communities. The death of Sahar Khodayari, or "Blue Girl, " an Iranian woman who committed suicide after being sentenced to prison for appearing in a sports stadium dressed as a man, is one such event that became a collective trauma. The current study sought to examine the collective trauma reaction among Farsi‐speaking Twitter users in response to Khodayari's death as represented in public tweets. The overall pool of data consisted of 8, 653 tweets containing at least one of four hashtags (i.e., #BlueGirl, #Blue_Girl, , # #), posted September 9–24, 2019, as well as 603 tweets posted on the anniversary of the event 1 year later. Using thematic analysis, we identified three main themes within these public tweets representing different responses to Khodayari's death: social justice, awareness, and process . In undemocratic countries, like Iran, where there are limited free physical spaces for public gatherings, social media provides a platform for people to come together after tragic events to express emotions and discuss thoughts and actions. The present findings demonstrate that Twitter allowed Farsi‐speaking users to demand social justice, share awareness about #BlueGirl, and process their emotions and thoughts accordingly. Therefore, social media may provide a window into the collective trauma experience, and it may also serve as a new mode of studying trauma on new platforms.